The Relationship Between Childhood Maltreatment and Sexual Coercion Proclivity in Women - Dean, Christina Renee (2017)
Researchers have explored the effects of sociocultural factors on male and female sexual expression, as well as the relationship between sexual objectification and overall sexual well-being; however, few scholars have focused on how, when combined with early experiences of childhood maltreatment, such factors can result in increased long-term risks for a variety of concerns that may impede the development of healthy relationships in women. This quantitative study explores the relationship of childhood maltreatment and sexual coercion proclivity in adult women. The purpose of this study was to measure self-reports of 1 or more experiences with childhood maltreatment (i.e., physical, sexual, or emotional abuse or neglect) to determine if it is significantly correlated with sexual coercion (physical or verbal sexually aggressive behaviors as well as nonverbal or psychological sexually coercive behaviors) in adult women. The differences in the incidence of self-reported experiences of sexual aggression in 211 female participants recruited via an online survey over a 7-day period were explored to examine if there is a relationship between the development of sexually coercive behaviors as a result of their self-reported experiences of childhood maltreatment. Data were collected using the Qualtrics database and indicated a positive correlation between childhood maltreatment and sexual coercion. Positive social change implications resulting from this research are the inclusion of another professional perspective on childhood maltreatment and sexual coercion, providing information to improve existing public health education and training forums, preventing or reducing the potential negative effects of childhood maltreatment, and ultimately improving the delivery of competent mental health services to all clients